Parenting styles and family counselling. Towards a holistic and multidisciplinary conceptualisation that responds to the demands of the 21st century (Mayéutica Revista Científica de Humanidades y Artes, 2022)
Nowadays, the family faces multiple psychosocial processes that threaten its wellbeing, as well as the timely functioning of each of its members. These aspects, as part of the tasks of family counselling, imply the integral accompaniment in which parents and children manage to face the resolution of their needs, the management of their emotions and the construction of positive attachment bonds that dynamize individual and collective behaviour. In view of the above, this essay, as a result of a documentary review, shows a theoretical journey that integrates diverse perspectives whose objective is to substantiatea holistic and multidisciplinary conceptualisation of parenting styles and family orientation, which favours the adoption of positive habits and the substitution of harmful practices that hinder the overcoming of obstacles, the confrontation of personal needs and competitiveness in order to achieve the consolidation of individual characteristics that drive the evolutionary development of parents and children. It is concluded that the possibilities for change, adjustment and transformation involve counselling in the adoption of parenting styles in which the development of autonomy, interdependence and coherent personality development are privileged.
Keywords: counselling; holistic wellbeing; family counselling; parenting styles; psychosocial development